Adapting Multiple Ground Improvement Techniques for Uniform Performance over Heterogeneous Natural and Modified Overburden - Michael J. Marasa (Deep Foundations Institute, 2017)
"Geotechnical engineering and construction primarily relies on the subsurface characteristics of the particular site; however, obtaining both accurate and precise information on those features is challenging due to the numerous factors involved in testing procedures used to analyze varying site geology. This includes a detailed and thorough geotechnical investigation to understand the site conditions, allowing the implementation of the most practical and economical solution.This paper presents a case history of the installation of wick drains and construction of aggregate piers on the site of a large facility to be constructed in Memphis, Tennessee. Throughout intensive subsurface investigations, highly variable soils were encountered, requiring settlement control and increased bearing capacity. This paper will discuss the design and installation of the systems constructed, and procedures and execution of the work to ensure design specifications were achieved.BackgroundA 1.4 million square foot expansion directly adjacent to an existing 1.1 million square foot distribution facility in Memphis, Tennessee was planned to serve as a centralized facility for increased production. The first phase of construction included an 858,000 square foot warehouse and parking lot for approximately 400 trucks to the north of the existing structure. The anticipated column load for the warehouse was 125 kips; slab design bearing pressures ranged from 200 to 500 pounds per square foot (psf) and elevations ranged from EL. 264 to 282. Parking lot elevations ranged from EL. 264 to 290, requiring a design life of 10 years with an estimated 100 in- and out-bound trucks daily and maximum weight of 80 kips per truck. The second phase of construction took place east of the existing structure, and included a 794,000 square foot multi-level warehouse, a 100,000 square foot office, and additional employee parking. The anticipated column load for the second warehouse was 225 kips and slab design bearing pressures ranged from 200 to 500 psf. Elevations ranged from EL. 267 to 282. Anticipated column loads from the office were 25 125 kips, with slab design bearing pressures ranging from 100 to 200 psf. Due to the varying elevations within each planned footprint, up to 18 feet of new fill was required to match the existing structure’s finished floor elevation (FFE) at EL. 282."